Idioms of resilience: Mental health and migration in India. (December 2022) - Raghavan, Raghu; Brown, Brian; Coope, Jonathan; Crossley, Mark; Sivakami, Muthusamy; Gawde, Nilesh; Pendse, Tejasi; Jamwal, Saba; Barrett, Andy; Dyalchand, Ashok; Chaturvedi, Santosh; Chowdary, Abhijeet; et al.
Background: Resilience has proved to be a versatile notion to explain why people are not defeated by hardship and adversity, yet so far, we know little of how it might apply to communities and cultures in low to middle income countries. Aim: This paper aims to explore the notion of resilience in cross-cultural context through considering the lived experience of internal migration. Methods: A sample of 30 participants with experience of migration was recruited from a low-income slum dwelling neighbourhood in the city of Pune, India. These individuals participated in biographical narrative interviews in which they were encouraged to talk about their experience of migration, their adaptation to life in their new environment and making new lives for themselves. Results: Participants referred to a variety of intra-individual and external factors that sustained their resilience, including acceptance of their circumstances, the importance of memory, hope for their children's futures as well as kindness from family friends and community members and aspects of the physical environment which were conducive to an improvement in their lives. Conclusions: By analogy with the widely used term 'idioms of distress', we advocate attention to the locally nuanced and culturally inflected 'idioms of resilience' or 'eudaemonic idioms' which are of crucial importance as migration and movement become ever more prominent in discussions of human problems. The nature and extent of people's coping abilities, their aspirations and strategies for tackling adversity, their idioms of resilience and eudaemonic repertoires merit attention so that services can genuinely support their adjustment and progress in their new-found circumstances.